Genetski dejavniki v povezavi z amiotrofično lateralno sklerozo - Vrabec, Katarina (Zdravniški vestnik, 2015)
Amyotrophic lateral sclerosis (ALS) is a rare complex neurodegenerative disease characterized by degeneration of motor neurons in the cerebral cortex, brainstem and spinal cord. The disease mainly occurs in adults, typically between 50. and 60. years and presents with symptoms like muscular weakness, atrophy and later on paralysis which lead to death due to respiratory failure within 2-5 years from onset and remains incurable. The symptoms typically start in the muscles of arms or legs (spinal onset) or bulbary (bulbar onset). Most ALS cases are sporadic although about 5% are familiar. Genetic factors contribute to the disease in sporadic form as well as in familial form. Mutations have been found in 116 genes among which SOD1, TARDBP, FUS and C9ORF72 are represented in highest frequencies. Besides those four genes we are also describing 13 other genes involved in the disease process. Oligogenic model has been proposed for ALS that considers mutations in two or more genes in one patient. We emphasize the convergence between hereditary and sporadic form, which are clinically inseparable, and other neurodegenerative diseases that share with ALS genetic and clinical characteristics. Because about 2/3 of familial cases and only about 11% of sporadic cases are explained by mutations the research have been aimed at discovering new candidate genes using genome %wide association studies and at the epigenetic causes of the disease. We have recently completed the first representative genetic analysis of patients with ALS in Slovenia and research on methylation and microRNAs is currently in progress.
Keywords: ALS causative genes; ALS predisposing genes; amiotrofična lateralna skleroza; epigenetics; genetski dejavniki